RANCANG BANGUN SISTEM PEMANTAU PENGGUNAAN ENERGI LISTRIK - Zurnawita Zurnawita; Cipto Prabowo (ITP Press)
Lighting and temperature regulation in a room greatly affect the effectiveness of the energy consumption in a building, we need a system for monitoring so that the energy consumed in accordance with the rules governing its use based on already made.Difficulty in realizing the energy monitoring system caused by the position of the measured object is located at some distant point. Wireless sensor network is one of the solutions so that objects can transmit measured data to the server via Wireless network. With this system is expected to be implemented in a larger scale so that it can be used as the basis of an internal energy audit so that the identification of energy saving opportunities can be done. Keywords: Energy monitoring systems, wireless sensor networks, servers, energy audits